(untitled) (Interdisciplinary Research in Education, 2021)
The fundamental importance of education is to unlock, reveal or make evident the unique potential of students. It is often regarded as a synonym for learning and is a product of experience. Education is also considered a restructuring or reorganization of experience to build new knowledge.As a lifelong learning process, education lasts from birth to death, and schools are not the only institutions that provide education. The role of educational institutions in providing quality education is by no means sufficient. Continued research and development activities are always relevant in this context.Learning involves continuous and constant changes in experience, ideas, knowledge, attitudes and skills, all complemented by homes, communities, religions, the media, etc., but educators innovate in this regard by considering development that can do a lot to come up with ideas. The present sixth volume, Issue 2 of Interdisciplinary Research in Education includes fourteen original articles. This is an attempt to address ongoing changes in the education sector, including both empirical research and desk reviews that help expand existing knowledge and understanding, especially in the areas of curriculum, pedagogy and education management.